GC-MS Analysis of Non-Polar Fractions of Leaves, Stems and Roots of Pisonia grandis R.Br. - Poongothai Gopal; Shubashini K. Sripathi; Indumathi P (International Journal of Phytomedicine, 2013)
The present investigation was designed to explore the secondary metabolites present in the petroleum ether extract of leaves, stems and roots of Pisonia grandis R.Br. using gas chromatography-mass spectrometry (GC-MS). Known quantity of shade dried and pulverized parts of Pisonia grandis were extracted with pet-ether at reflux temperature for 6 h. The extracts were concentrated under vacuum and the concentrated extracts designated as PGSP, PGRP and PGLP were subjected to GC-MS analysis. The GC-MS analysis revealed the most prevailing phytoconstituents as n-hexadecanoic acid (palmitic acid), 6-octadecenoic acid (petroselenic acid), 9-octadecenoic acid (oleic acid), 2,3-bis-[(9E)-9-octadecenoyloxy]propyl (9E)-9-octadecenoate (9-octadecenoic acid 1,2,3-propanetriyl ester) and phytol in the extracts. The presence of various therapeutically important metabolites justifies the use of the plant for various ailments by tribals and traditional healers.